The Unsettling Event of an Enigma, *to be forever or never to have been - Pericleous, Vicky; Zografos, Vasilis (My University, 2023)
Vicky Pericleous – Vasilis Zografos The unsettling event of an enigma (to be forever, but never to have been*) Lola Nikolaou gallery Opening: Tuesday 3 October 2023 from 18:00 to 22:00 Duration 3-27 October Curation: Vicky Pericleous – Vasilis Zografos The exhibition is developed through a subversive and evocative dialogue towards a visual investigation that primarily, seeks to choreograph the invisible, in-between space. The dialectic that is, space between the works, and consequently, the space, which is constituted through the viewers’ interpretations. The site-specific installation emerges in space through a set of spatiotemporal expansions, folds and compactions. All these, a product of visual performativities and speculations, could finally, be inscribed as the after-sound of one or multiple events. The title of the exhibition recalls Man Ray’s work ‘L’Enigme d’Isidore Ducasse’, 1920 and the subtitle is taken from Jorge Luis Borges’ poem ‘The Enigmas’ from the collection ‘Jorge Luis Borges, Selected Poems, 1923-1967’ of 1972. This collaborative installation, with the intention to engage the invisible as real and the immaterial as vital, in order to explore and expand the visible and the perceptual, constitutes, essentially, a political act. The enigmatic object in Ray’s work critically reference the emblematic for surrealism, phrase by Isidore Ducasse (1809-87), better known as Comte de Lautréamont, ‘‘Beautiful as the accidental encounter, on a dissecting table, of a sewing machine and an umbrella’, re-surfaces on the dissecting table of today’s – labyrinthine- worlds, as a ghostly reminder, in present tense. A reminder of the opening or the possibility of art –not only- towards a surprising image or a mystery-image, but towards the rising of this in-between dialectical space, -between objects and subjects-, as a surprising space or a mystery-space. This intangible but active space, engages in the production of the exhibition as a vital space and as a space of multiplicities. Its substances, could, potentially, re-engage, deviate or re-locate, visually and perceptually, the works themselves, into other –allusive- views and propositions.
Keywords: Arts